The Mediating Effect of Life-style Behaviors on the Association Between Personality Traits and Cardiovascular Disease Mortality Among 29,766 Community-Dwelling Japanese - Narita, Mamoru (Psychosom Med, 2020)
OBJECTIVE: Personality traits have been associated with an increased risk of cardiovascular disease (CVD) mortality as well as life-style–related cardiovascular risk factors. However, the mediating effects of life-style behaviors in the association between personality factors and CVD mortality remain insufficiently understood. The aim of the present study was to examine the mediating effect of life-style behaviors on the association between personality traits and CVD mortality. METHODS: We conducted a prospective cohort study of 29,766 Japanese adults aged 40 to 64 years at the baseline and followed them up for 20.8 years from 1990 to 2011. Personality was measured using the Japanese version of the Eysenck Personality Questionnaire – Revised Short Form in 1990. We estimated the multivariable hazard ratio and 95% confidence interval for CVD mortality using Cox proportional hazards models, and explored the mediating effects of life-style behaviors (smoking, drinking, body mass index, and time spent walking) on the association between personality traits and CVD mortality. RESULTS: We documented 1033 deaths due to CVD during 562,446 person-years of follow-up. Psychoticism represents tough-mindedness, aggressiveness, coldness, a lack of deliberateness, and egocentricity. After adjusting for confounding variables, higher psychoticism was associated with CVD mortality (base model hazard ratio = 1.36, 95% confidence interval = 1.14–1.61, p trend < .001). All the life-style behaviors together mediated this association by 19.2%, with smoking having the greatest effect at 15.7%. For the other personality traits, no significant associations with CVD mortality were found. CONCLUSION: The present study demonstrated that life-style behaviors, especially smoking, partially mediate the association between psychoticism and CVD mortality.